IMPACT OF MEAL REPLACEMENT ON THE HEALTH STATUS OF TYPE II DIABETES - Gupta, Manorama (International Journal of Current Pharmaceutical Research, 2014)
Diabetes mellitus is one of the pandemic disorder affecting approximately 347 million people in world. The WHO identified and announced India as the capital of Diabetes. Food products that can induce a slow release of glucose are the demand for managing diabetes. Hence researchers are accelerated to bring into focus the same; so we planned to prepare a low glycemic roti for the management of diabetes which is low cost, high in fiber, low glycemic index and glycemic load value. The glycemic index and glycemic load of the product was assessed by monitoring the rises in blood glucose after a 50g of portion was fed to 15 healthy subjects. The glycemic index of hypoglycemic roti is 53%. The impact of formulated roti was assessed at 1% significance among all diabetic individuals.